Relationship between Family Support and Compliance in Taking Antiretroviral (ARV) Drugs with the Incidence of Opportunistic Infections in Children With HIV/AIDS - Dwi Budiyati; Nyimas Heny Purwati; Anita Apriliawati; Sri Istiyani; Fitriarini Fitriarini; Siti Maemun (Indonesian Journal of Global Health Research, 2025)
Opportunistic infections are one of the leading causes of morbidity and mortality in children with HIV/AIDS. These infections can be prevented through lifelong adherence to antiretroviral (ARV) therapy and strong family support. This study aims to analyze the relationship between family support and adherence to ARV medication with the incidence of opportunistic infections in children with HIV/AIDS. The study employed a cross-sectional design. The respondents were 50 children with HIV/AIDS receiving treatment at RSPI Sulianti Saroso Jakarta, selected using purposive sampling. Data were analyzed using the Chi-square test and Logistic Regression for multivariate analysis. The results indicated a significant relationship between family support including emotional support (p = 0.002), appraisal support (p = 0.001), instrumental support (p = 0.001), and informational support (p = 0.009) as well as ARV adherence (p = 0.001) with the incidence of opportunistic infections. Multivariate analysis revealed that instrumental support had the greatest influence, with p = 0.012 and Exp (B) = 1.458, indicating that children with low instrumental support had a 1.46 times higher risk of developing opportunistic infections compared to those with adequate support. There is a significant association between family support and ARV adherence with the occurrence of opportunistic infections in children with HIV/AIDS. Strengthening family-based nursing interventions focus on empowering parents to provide instrumental support such as meeting nutritional needs, ensuring access to healthcare services, and supervising ARV adherence is essential to improving the quality of life of children with HIV/AIDS.